THE INFLUENCE OF SOCIAL MEDIA ON PUBLIC PARTICIPATION IN ENVIRONMENTAL ISSUES - Elva Rinda (Multidisciplinary Indonesian Center Journal (MICJO), 2025)
Social media has transformed the global communication landscape and has become a vital instrument in increasing awareness and public participation on various environmental issues. This study aims to analyze the role and impact of social media in encouraging public engagement in environmental movements, both at the local and global levels. Using a qualitative approach with a combination of systematic literature analysis and multiple case studies, this research examines how social media platforms facilitate the dissemination of environmental information, promote collective action, and create spaces for discussions on environmental sustainability. The findings indicate that social media plays a significant role in mobilizing individuals to take concrete actions on environmental issues through three main mechanisms: (1) democratization of environmental information, (2) facilitation of the formation of environmental communities, and (3) acceleration of collective responses to urgent environmental issues. However, the study also identifies critical challenges, including the spread of false information, digital divide, and slacktivism phenomena that may hinder the effectiveness of digital environmental campaigns. Further analysis reveals that the effectiveness of social media use in environmental campaigns heavily depends on content strategies, timing, and the involvement of environmental influencers. The study also finds a positive correlation between the intensity of social media usage for environmental purposes and the level of public awareness and active involvement in environmental preservation. Additionally, the research highlights the significant role of social media as a catalyst for pro-environmental behavior among younger generations. These findings contribute significantly to the development of more effective environmental communication strategies in the digital era, emphasizing the importance of digital literacy in the context of environmental activism. The study recommends combining social media power with concrete actions to achieve optimal impact in addressing environmental challenges.